Morphing cholinesterase inhibitor amiridine into multipotent drugs for the treatment of Alzheimer's disease - Mezeiova, Eva; Prchal, Lukas; Hrabinova, Martina; Muckova, Lubica; Pulkrabkova, Lenka; Soukup, Ondrej; Misiachna, Anna; Janousek, Jiri; Fibigar, Jakub; Kucera, Tomas; Horak, Martin; Makhaeva, Galina F; et al. (Biomedicine & pharmacotherapy, 2024)
The search for novel drugs to address the medical needs of Alzheimer's disease (AD) is an ongoing process relying on the discovery of disease-modifying agents. Given the complexity of the disease, such an aim can be pursued by developing so-called multi-target directed ligands (MTDLs) that will impact the disease pathophysiology more comprehensively. Herewith, we contemplated the therapeutic efficacy of an amiridine drug acting as a cholinesterase inhibitor by converting it into a novel class of novel MTDLs. Applying the linking approach, we have paired amiridine as a core building block with memantine/adamantylamine, trolox, and substituted benzothiazole moieties to generate novel MTDLs endowed with additional properties like N-methyl-d-aspartate (NMDA) receptor affinity, antioxidant capacity, and anti-amyloid properties, respectively. The top-ranked amiridine-based compound 5d was also inspected by in silico to reveal the butyrylcholinesterase binding differences with its close structural analogue 5b. Our study provides insight into the discovery of novel amiridine-based drugs by broadening their target-engaged profile from cholinesterase inhibitors towards MTDLs with potential implications in AD therapy.
Keywords: Butyrylcholinesterase; Ligands; Alzheimerova nemoc; butyrylcholinesterasa; Acetylcholinesterase; lidé; cholinesterasové inhibitory; aminochinoliny; Cholinesterase Inhibitors; Aminoquinolines; acetylcholinesterasa; Alzheimer Disease; ligandy; Humans